Front Cover. Issue 9 (13th August 2020) - Bakker, Victoria J.; Sillett, T. Scott; Boyce, Walter M.; Doak, Daniel F.; Vickers, T. Winston; Reisen, William K.; Cohen, Brian S.; Hallworth, Michael T.; Morrison, Scott A.
Abstract : The cover image is based on the Original Article Translocation with targeted vaccination is the most effective strategy to protect an island endemic bird threatened by West Nile virus by Victoria J. Bakker et al., https://doi.org/10.1111/ddi.13109 .